Estimación de la prescripción de medicamentos empleados para el tratamiento del cáncer de mama que entraron al plan de beneficios en salud (2023)
Adapt the IQVIA company model as a tool for the Roche data analytics area to estimate and consult the number of drug prescriptions used for the treatment of breast cancer, included in the Health Benefits Plan.